ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ-45 BURSA EFEK INDONESIA PERIODE 2012-2016 - Erna Ambaryani, 14.05.52.0015; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
Dividend payment policy is a very important policy, because it will involve two parties namely shareholders and management companies that can have different interests. The dividend policy determines the placement of profits, which is between paying to shareholders and reinvesting the company. sfs purpose of this research is to examine the factors influencing dividend payout ratio at the company listed in Index LQ-45 by using Current Ratio (CR), Debt to Equity Ratio (DER), Return On Asset (ROA) and Firm Size.  The data in this research is annual report (Annual Report). The sample is determined by Purposive Sampling technique. This research uses 24 companies that are included in category LQ-45 in Indonesia Stock Exchange (BEI) as sample.  The result of this research shows that Current Ratio and Debt to Equity Ratio have significant negative effect to Dividend Payout Ratio, while Return On Asset and Firm Size have positive significant effect to Dividend Payout Ratio.Keywords:Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), Firm Size., Dividend Payout Ratio (DPR).